Study on the Design and Optimization of a Portable Monitoring and Auxiliary Treatment Device for Upper Extremity Lymphedema–Focus on the Rehabilitation Function of the Device - Yanmin, Xue; Xuyang, Zhang; Wen, Yan; Suihuai, Yu; Sinan, Li (Frontiers in Bioengineering and Biotechnology, 2021)
Female patients suffer from the risk of upper limb lymphedema after Breast cancer removal surgery. At present, the detection and adjuvant treatment of this disease are not convenient enough, leading to delay of the disease and increase the burden of patients. This paper presents a portable monitoring and treatment device for upper extremity lymphedema, enabling patients to monitor the symptoms of upper limb lymphedema and auxiliary rehabilitation. This design utilizes the arm circumference measurement and contrast method to realize symptom monitoring. The device realizes the auxiliary rehabilitation using the regional pressure method to imitate the traditional manual lymphatic drainage technology. According to the MRI images of volunteers' upper limbs, the upper arm and forearm's finite element models are reconstructed in ANSYS. The static simulation experiment is completed. The working mode and parameter design of each rehabilitation module of the device are obtained. The experimental results show that the integrated design principle of monitoring and treatment proposed in this paper has good feasibility, has auxiliary rehabilitation effect and meets the principle of human comfort. The device can help patients find lymphedema in time and implement auxiliary treatment, which can effectively avoid further deterioration of lymphedema.